Prognostic factors in stereotactic body radiotherapy of lung metastases Prognostische Faktoren bei der stereotaktischen Strahlentherapie von Lungenmetastasen - Borm, K. J.; Oechsner, M.; Schiller, K.; Peeken, J. C.; Dapper, H.; Munch, S.; Kroll, L.; Combs, S. E.; Duma, M. N. (Strahlentherapie und Onkologie, 2018)
Purpose: The aim of this study was to evaluate prognostic factors in patients with lung metastases who undergo lung stereotactic body radiotherapy (SBRT). Materials and methods: A total of 87 patients with 129 lung metastases who underwent SBRT between November 2004 and May 2012 were enrolled in this retrospective study. The patient collective consisted of 54 men (62.1%) and 33 women (37.9%); the median age was 65 years (range 36–88). The Karnofsky performance index was ≥70% (median 90%) for all cases, but one (60%). Adverse effects were categorized using the CTCAE 4.0 classification system. Retrospective analyses regarding patients’ characteristics, progression-free survival (PFS), overall survival (OS), disease-specific survival (DSS), and local tumor control rates (LTC) were performed. Results: On univariate and multivariate analysis OS, DSS, and PFS were significantly (p < 0.05) better for patients with ≤3 lung metastases; no extrathoracic metastases at the time of the SBRT; a gross tumor volume (GTV) <7.7 cm3 and patients that received a staging that included positron emission tomography with fluorine 18 fluorodeoxyglucose/computed tomography (FDG-PET/CT) imaging. Furthermore, a longer OS was observed if newly diagnosed metastases during follow-up were limited to the lung (median survival: 43.7 months versus 21.7 months; p = 0.023). Conclusion: The number and pattern of metastases, and the size of the target volume are strong predictors for the outcome of patients receiving SBRT of lung tumors. FDG-PET/CT should be part of pretherapeutic staging before SBRT.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Lung metastasis; PET-CT; Prognostic factors; SBRT; Staging